DATA-DRIVEN MARKETING COMMUNICATIONS: THE CRUCIAL ROLE OF ACCOUNTING INFORMATION SYSTEMS - Loso Judijanto; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Data-driven Marketing Communications supported by Accounting Information Systems (AIS) is a strategic approach to marketing that utilises financial and non-financial data generated by AIS to design, execute and evaluate marketing communications activities. This approach integrates accurate and structured accounting information into marketing strategy, enabling more informed decision-making, more effective message personalisation, and more accurate measurement of marketing performance. By utilising AIS, companies can optimise the allocation of marketing resources, improve campaign effectiveness, and achieve higher return on investment (ROI) in their marketing activities. The results show that AIS plays a crucial role in providing accurate and structured data that can be used for consumer behaviour analysis, market segmentation, and measurement of marketing campaign effectiveness. The integration of AIS with marketing information systems enables better personalisation of marketing communications, more efficient resource allocation, and improved marketing ROI.